Further mobility enhancements for 5G-advanced and beyond - Jedrzej Stanczak; Umur Karabulut; Ahmad Awada; Ali Karimidehkordi; Niko Kolehmainen; Alperen Gundogan (International Journal of Electronics and Telecommunications)
The study on mobility is an inherent part of any generation of cellular technology. It is aimed at ensuring robust, reliable, and interruption-free handover of the mobile user connection. Such continuous improvement is necessary as the service requirements become more stringent which urge the mobility to meet the highest performance expectations. In this paper, it is described how such requirements are to be achieved by the 3GPP Release 18 components. It begins with the introduction to the world of mobility, covering the solutions that have been designed since the first generation of New Radio (NR). Then improvements pursued in consecutive 3GPP releases are outlined. Selected areas for Release 18 mobility enhancements have been evaluated using 5G-compliant system-level simulations and results thereof are presented below. These include wrong Primary Secondary Cell (PSCell) preparation in Conditional Handover (CHO) and the impacts of secondary cell setup delay in Dual Connectivity (DC). It is shown that preparing multiple PSCells in CHO ensures the user accesses the right cell in up to 96% of cases.